PENGARUH VARIASI KOMPOSISI CAMPURAN MORTAR TERHADAP KUAT TEKAN - Heri Sujatmiko (Yayasan Nusantara Hasana Berdikari, 2024)
In Indonesia, especially the use of mortar is very popular. Where in constructing a concrete construction, mortar is always used as part of a construction. But the process of making mortar mixtures is sometimes less true in making mixed society in terms of economics and quality. Based on the description, the authors are interested to conduct research on the influence of variation of mix mortar composit ion on compressive strength, with two samples of cement type. Mortar uses mortar from Semen Gresik and from Semen Holcim without any additional materials. research shows that the increasing composition of sand, the compressive strength of mortar decreases. Where the compressive strength of mortar at 28 days for mixed composition variation using Semen Gresik 1: 4 of 9.5 Mpa; 1: 5 of 11.68 MPa; 1: 6 of 7.86 MPa and 1: 7 of 5.31. Whereas the compressive strength value for mortar using Semen Holcim was 13.38 Mpa, respectively; 12,95 Mpa; 7.65 Mpa and 3.19 Mpa. The result of water absorption on the mortar by adding the amount of sand will result in a greater decrease in the compressive strength of each mortar variation.So that the mixture of plaster walls or specimens to adhere the recommen ded flooring and mortar walls of simple mortar is a mixture composition with the ratio of cement: sand 1: 5 for Semen Gresik and 1: 4 and 1: 5 for Holcim Cement.